A light-weight oblivious transfer protocol based on channel noise. Issue 1 (2nd January 2017) - Guan, Albert; Tzeng, Wen-Guey
ABSTRACT: A novel and computationally light-weight protocol for establishing oblivious transfer is presented in this paper. The proposed protocol is based on the unpredictable noise in the communication channels. The security of our oblivious transfer protocol does not depend on computationally hard problems. We show that the receiver has no information about the other secret due to unpredictable noise in the communication channel. Furthermore, the protocol does not need heavy computations. Therefore, our protocol is more suitable for the devices which have only limited computing resources.